Long term dental transversal stability of Class II division 1 treated with cervical headgear - Márcio Bastos de OLIVEIRA; Jean Nunes dos SANTOS; Vanessa Mascarenhas LIMA; Tiago Fonseca Lima da FONTE; Telma Martins de ARAUJO; Carlos Jorge VOGEL; Emanuel Braga RÊGO (Dental Press Editora, 2022)
ABSTRACT Introduction: In several conditions, outcome stability is a great challenge for Orthodontics. Previous studies have reported that relapse commonly occurs along the years after orthodontic treatment finishing. Objective: The aim of the present study was to evaluate in the long-term transversal dental arch changes of Class II division 1 patients treated with cervical headgear and fixed appliance. Methods: Plaster study casts of 20 patients treated with cervical headgear without dental extractions were 3D-scanned and evaluated in three distinct times: initial (T1), immediate post-treatment (T2) and long-term retention (T3 - minimum 20 years). Transversal teeth distance of maxillary and mandibular canines, premolars and first molars were measured. Results: A statistically significant increase during treatment was observed for all maxillary teeth transversal distances (p< 0.05). In turn, a significant reduction was observed in the long term (p<0.05). For the mandibular teeth, canine transversal distance presented statistically significant constriction in the retention period (p<0.05). Mandibular first molars distance was significantly expanded by treatment (p<0.05) and remained stable in the long term. The changes observed for the other teeth or other times were considered not statistically relevant. Conclusions: For the accessed sample, transversal changes occurred during treatment and retention phases in Class II division 1 patients treated with cervical headgear and fixed appliance. Relapse was considered statistically relevant, even with the institution of a retention protocol.